Analysis of the Film The Life of Others, from the Transactional Analysis and Bargaining Theory - Valbuena de la Fuente, Felicísimo (CIC. Cuadernos de Información y Comunicación, 2007)
The author has chosen one of the films that have attracted more interest of the spectators in the last years and undertakes a line of interpretation that has applied to other films. From two powerful intellectual frameworks, he aspires to unravel the motives behind the communicative changes in interpersonal relationships.